UPAYA MENCETAK PESERTA DIDIK YANG BERKARAKTER - Siti Sri Rahayu (Basastra, 2012)
Abstract Character education has always attracted the attention of many. Gunda some sense of the people of Indonesia to the arrogant behavior of the recently demonstrated through a glass screen or print media, such as mutual blasphemy, will not budge, and other bad behavior invites human concerns of education in Indonesia. School as a young printer intermediary institutions of the nation must take responsibility against the erosion of a sense of empathy, respect, and sense of community that has become characteristic of Indonesian society since ancient times our time. Regarding the note about how the real effort should be made to print the character of students in the midst of the hustle and bustle of politics and genjarnya flow of information through television, internet, and other means. Curriculum as a design in education are well positioned with respect to the true character education efforts have been accommodated in the particular subject. Therefore, the suggestion that dapata do of course expect a teacher to enhance the professionalism of one of them realized in the form of examples and behaviors that can make students comfortable in devoting the problems faced and the teacher can catch any strange behavior of the learners.   Kata kunci: peserta didik, pendidikan berkarakter, guru yang profesional